An improved modulation scheme for dual active bridge converters - Lim, Tian Fu (Nanyang Technological University, 2021)
Dc-dc converters are considered as one of the important elements of the power systems. They are utilized for the integration of the renewable energy sources to the microgrid, consumer electronics to provide suitable voltage levels, battery charging and discharging in electric vehicles (EVs) and so on. There are different types of dc-dc converters available. One of the popular and widely used converter is the dual active bridge (DAB) converter. The regulation of the power flow through the dual active bridge - isolated bidirectional dc-dc converters (DAB-IBDC) are more advance compared to their counterpart, the non-isolated dc-dc converters. For regulating the power flow of DAB converters, the single phase shift (SPS) modulation scheme is the most popular one. Through adjusting the outer phase shift between the voltage waveforms of the two H-bridges, the direction and magnitude of the transferred power can easily be controlled. Although SPS modulation method is easy to implement, it produces the dual side circulating currents in DAB converters. It is known that circulating currents will taper the effectiveness of the DAB converter and shorten the lifecycle of terminal energy-storing units due to frequent charging and discharging phenomenon. Therefore, it is significant to minimise and eventually eliminate the dual-dc side circulating current in DAB converters. Therefore, the purpose of this project is to study the operation principle of DAB converters with the SPS modulation scheme and understand the essential reason for causing the circulating currents. Secondly, to study, simulate and analyse the other advanced modulations, namely double phase shift (DPS) and triple phase shift (TPS) methods. The study also includes the comparison of SPS, DPS and TPS modulation methods and their effects on the operation of DAB converters. Lastly, to determine the ideal modulation methodology to fully eliminate the circulating current and curb the negative impacts of the circulating current.